Biologically Active Compounds Present in Tobacco Smoke: Potential Interactions Between Smoking and Mental Health - Hong, Sa Weon; Teesdale-Spittle, Paul; Page, Rachel; Ellenbroek, Bart; Truman, Penelope (Frontiers in Neuroscience, 2022)
Tobacco dependence remains one of the major preventable causes of premature morbidity and mortality worldwide. There are well over 8000 compounds present in tobacco and tobacco smoke, but we do not know what effect, if any, many of them have on smokers. Major interest has been on nicotine, as well as on toxic and carcinogenic effects and several major and minor components of tobacco smoke responsible for the negative health effects of smoking have been elucidated. Smokers themselves report a variety of positive effects from smoking, including effects on depression, anxiety and mental acuity. Smoking has also been shown to have protective effects in Parkinson’s Disease. Are the subjective reports of a positive effect of smoking due to nicotine, of some other components of tobacco smoke, or are they a manifestation of the relief from nicotine withdrawal symptoms that smoking provides? This mini-review summarises what is currently known about the components of tobacco smoke with potential to have positive effects on smokers.